Long-term insulin treatment restores cardioprotection induced by sufentanil postconditioning in diabetic rat heart. Issue 6 (March 2016) - Zhang, Yuwen; Zhang, Lei; Gu, Erwei; Zhu, Bingqing; Zhao, Xianya; Chen, Jingjing
Sufentanil, a commonly used opioid analgesic, could mimic ischemia postconditioning to attenuate ischemia reperfusion injury, but this effect might be hindered in diabetic animals by inhibition of glycogen synthase kinase-3β phosphorylation. Also, diabetes can abrogate the cardioprotection of sevoflurane (an inhaled anesthetic) against ischemia reperfusion injury, and short-term insulin treatment does not restore protection by sevoflurane postconditioning. We hypothesized that long-term insulin treatment might restore the cardioprotective effect of sufentanil postconditioning in diabetic rats via phosphorylation of glycogen synthase kinase-3β. Streptozotocin (55 mg/kg)-induced diabetic rats received insulin (Novolin N, 6–8 u/d) for two days or two weeks, then were exposed to 30-min ischemia and 120-min reperfusion. Sufentanil postconditioning was performed 5 min before the onset of reperfusion. Controls included non-diabetic rats, sham surgery for ischemia/reperfusion, and sufentanil vehicle. Infarct size, cardiac troponin I, and phosphorylated glycogen synthase kinase-3β were examined. Sufentanil postconditioning reduced infarct size by 46% in non-diabetic rats ( P < 0.001), but diabetes prevented this protective effect. Two-day insulin treatment was not effective, but two-week treatment reduced infarct size by 45% ( P < 0.001), reduced cardiac troponin I by 33% ( P < 0.001), and increased phosphorylated glycogen synthase kinase-3β levels ( P < 0.001) in the diabetic sufentanil postconditioning group. In conclusion, sufentanil-induced cardioprotection was restored by long-term insulin treatment. The underlying mechanism may be increased phosphorylation of glycogen synthase kinase-3β.